Developmental Programming of Obesity and Metabolic Dysfunction: Role of Prenatal Stress and Stress Biology - Entringer, Sonja (2013)
Epidemiological, clinical, physiological, cellular and molecular evidence suggests the origins of obesity and metabolic dysfunction can be traced back to intrauterine life and supports an important role for maternal nutrition prior to and during gestation in fetal programming. The elucidation of underlying mechanisms is an area of interest and intense investigation. We propose that in addition to maternal nutrition-related processes, it may be important to concurrently consider the potential role of intrauterine stress and stress biology. We frame our arguments in the larger context of an evolutionary-developmental perspective that supports roles for both nutrition and stress as key environmental conditions driving natural selection and developmental plasticity. We suggest that intrauterine stress exposure may interact with the nutritional milieu, and that stress biology may represent an underlying mechanism mediating the effects of diverse intrauterine perturbations, including but not limited to maternal nutritional insults (undernutrition and overnutrition), on brain and peripheral targets of programming of body composition, energy balance homeostasis and metabolic function. We discuss putative maternal-placental-fetal endocrine and immune/inflammatory candidate processes that may underlie the long-term effects of intrauterine stress.